Łucja Charewiczowa jako badaczka i propagatorka historii regionalnej i lokalnej - Malczewska-Pawelec, Dorota (Wieki Stare i Nowe, 2019)
The text presents the scholarly and popular science output in the field of regional history produced by Łucja Charewiczowa, a female Lvovian historian of the inter -war period. There is a discussion of the most important works of the Researcher in this field, with special emphasis on their conceptualisation, construction, empirical approach and literary qualities. The outline also constitutes an attempt to present the peculiar nature of Charewiczowa’s writings in the context of the regional history works (the social, historical and economic orientation, a strongly marked presence of female figures, educational and patriotic aspects). Moreover, it also emphasises the research and narrative approaches of the Lvovian author which were ground -breaking in Poland.